External Validation of the Cancer of the Prostate Risk Assessment-S Score in Koreans Undergoing Radical Prostatectomy - Seong, Ki Taek (The Korean Urological Association, 2013)
PURPOSE: To evaluate the validity of the University of California San Francisco Cancer of the Prostate Risk Assessment-S score (CAPRA-S score), a biochemical indicator of recurrent prostate cancer that uses histopathologic data, in Korean prostate cancer patients. MATERIALS AND METHODS: A total of 203 prostate cancer patients who underwent radical prostatectomy between February 1997 and November 2010 were observed for longer than 6 months. The CAPRA-S score of 134 patients for whom records were available for preoperative prostate-specific antigen (PSA), pathologic specimen Gleason score, surgical margin, seminal vesicle invasion, extracapsular extension, and lymph node invasion were calculated. Biochemical recurrence was defined as repetitive measurement of PSA ≥0.2 ng/mL at least 6 months after surgery with at least a 4-week interval. The Cox proportional hazard model and Kaplan-Meier analysis were used for the statistical testing. RESULTS: The CAPRA-S scores were divided into nine groups. The 5-year disease-free survival rate was reduced as the CAPRA-S score increased compared with the group with a CAPRA-S score of 0-1. The CAPRA-S score in this study was more sensitive to biochemical recurrence than was the CAPRA score conducted at this institution (CAPRA-S concordance index, 0.776; CAPRA concordance index, 0.728). CONCLUSIONS: The CAPRA-S score is judged to be a useful tool for predicting the disease-free survival rate of Korean prostate cancer patients and is thought to assist in establishing postoperative management.